The Prognostic Role of the Platelet-Lymphocytes Ratio in Gastric Cancer: A Meta-Analysis - Xu, Zhengshui (PLoS One, 2016)
BACKGROUND: Systemic inflammatory parameters, such as the elevator PLR (platelet-lymphocyte ratio), the NLR (neutrophil-lymphocyte ratio) and the platelet count (PLT), have been found to be associated with the prognosis in gastric cancer; however, these results, especially those relating to the PLR, remain inconsistent. So we aimed to evaluate the prognostic role of the PLR in gastric cancer by conducting and presenting the findings of this meta-analysis. METHODS: We conducted a systematic literature search in PubMed, Embase and the Cochrane Library to evaluate the prognostic value of the PLR in gastric cancer. The quality of the included studies was evaluated using the Newcastle Ottawa Quality Assessment Scale (NOS). The hazard ratio (HR) /Odds Ratio (OR) and its 95% confidence were pooled using a random effects model. A funnel plot based on overall survival was used to evaluate the publication bias. RESULTS: It total, 8 studies comprising 4513 patients with gastric cancer met the pre-setting inclusion criteria. In comparison to the normal PLR, an elevated PLR was correlated with a higher risk of lymph node metastasis with an OR of 1.50 (95% Cl:1.24–1.82; I(2) = 17%) and serosal invasion (T3 +T4) risk with an OR of 2.01 (95% Cl: 1.49–2.73; I(2) = 55%), and an elevated PLR also increased the advanced stage (III +IV) risk with an OR of 1.99 (95% Cl: 1.60–2.46; I(2) = 28%). An elevated PLR was not a reliable predictor for OS with an HR of 0.99 (95% CI: 0.9–1.1; I(2) = 12%). CONCLUSIONS: An elevated PLR was correlated with a higher risk of lymph node metastasis, serosal invasion and advanced stage (III +IV) risk in gastric cancer; however, the PLR may not act as a negative predictor for the overall survival of gastric cancer.